New aspects of congenital melanocytic nevi. - Kinsler, V. (European Journal of Pediatric Dermatology, 2008)
A long-term (1988-2007) prospective study was carried out in 349 subjects with congenital melanocytic nevi (CMNs). Female sex, maternal smoking during early pregnancy and family history of CMNs were significant predisposing factors. A family history positive for CMNs was associated with a different type of CMN.